2015
DOI: 10.1007/s00190-015-0875-4
|View full text |Cite
|
Sign up to set email alerts
|

Blind source separation problem in GPS time series

Abstract: A critical point in the analysis of ground displacement time series, as those recorded by space geodetic techniques, is the development of data-driven methods that allow the different sources of deformation to be discerned and characterized in the space and time domains. Multivariate statistic includes several approaches that can be considered as a part of data-driven methods. A widely used technique is the principal component analysis (PCA), which allows us to reduce the dimensionality of the data space while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
104
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 82 publications
(105 citation statements)
references
References 27 publications
1
104
0
Order By: Relevance
“…In our case we tested the PCA approach and observed that most components were a mix of seasonal and postseismic signals. By contrast, different sources of deformation, which tend to be statistically independent from one another, tend to be represented by different components in an ICA (Gualandi et al, 2015). This approach is thus particularly well suited to separate the contributions due to tectonics and surface hydrology.…”
Section: Data and Signal Extractionmentioning
confidence: 94%
See 2 more Smart Citations
“…In our case we tested the PCA approach and observed that most components were a mix of seasonal and postseismic signals. By contrast, different sources of deformation, which tend to be statistically independent from one another, tend to be represented by different components in an ICA (Gualandi et al, 2015). This approach is thus particularly well suited to separate the contributions due to tectonics and surface hydrology.…”
Section: Data and Signal Extractionmentioning
confidence: 94%
“…The vbICA technique then allows us to determine the best reference frame onto which project the data in order to optimally separate the contribution of each singular source. We refer the interested reader to the Supplementary Material (Section S1) as well as to Choudrey (2002), Choudrey and Roberts (2003), and Gualandi et al (2015) for more details. We preferred an ICA over a more standard PCA as a PCA does not do well at separating different sources of deformation (e.g.…”
Section: Data and Signal Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 shows the location of the 14 stations considered in this study with respect to the fault position, while Figure s1 (Supplementary Materials) shows the GPS position time series. The detrended, filtered displacement time series are the input of an independent component analysis (ICA) performed adopting a variational Bayesian approach (vbICA, [23]) and modified in order to take into account missing data [24,25]. This method, applied to geodetic time series, performs a spatiotemporal separation of the geodetic data into a limited number of signals, subsequently interpreted as the actual physical sources that generated the observed displacements.…”
Section: Gps Datamentioning
confidence: 99%
“…Forootan andKusche (2012, 2013) argue that different physical processes generate statistically independent source signals that are superimposed in geophysical time series; thus, application of ICA likely helps separating (extracting) their contribution from the total signal. Therefore, in the recent studies (e.g., Awange et al 2014;Boergens et al 2014;Gualandi et al 2016;Ming et al 2016), ICA has been preferred over the ordinary extensions of the PCA/EOF approach, such as the rotated EOF (REOF) technique applied in, e.g., Richman (1986) and Lian and Chen (2012).…”
Section: Introductionmentioning
confidence: 99%